1973
DOI: 10.1542/peds.52.4.525
|View full text |Cite
|
Sign up to set email alerts
|

The Syndrome of Neonatal Copper Deficiency

Abstract: A syndrome of primary copper deficiency in a 6-month-old premature baby is described. Features which can be ascribed to lack of copper, include (1) a sideroblastic anemia resistant to other therapy, with vacuolation of erythroid and myeloid bone marrow cells, and iron deposition in the vacuoles and in some mitochondria; (2) neutropenia, especially segmentopenia, which was common and prominent; (3) long-bone changes on radiological examination, particularly osteoporosis with blurring and cupping of the metaphys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In this model, iron is finally secreted into milk by exocytosis of secretory vesicles at the apical membrane. The molecular entity that mediates iron oxidation after its transport by FPN remains unknown vulnerable to nutritional copper deficiency [127,128]. Moreover, toxic-milk (tx) mice pups die in the second week from severe copper deficiency due to low liver copper stores and low intakes from maternal copper-deficient milk [129].…”
Section: Copper Transport In the Mammary Glandmentioning
confidence: 99%
“…In this model, iron is finally secreted into milk by exocytosis of secretory vesicles at the apical membrane. The molecular entity that mediates iron oxidation after its transport by FPN remains unknown vulnerable to nutritional copper deficiency [127,128]. Moreover, toxic-milk (tx) mice pups die in the second week from severe copper deficiency due to low liver copper stores and low intakes from maternal copper-deficient milk [129].…”
Section: Copper Transport In the Mammary Glandmentioning
confidence: 99%
“…Hypocupremia is encountered in Menkes's disease and in the early stages of Wilson's disease, two rare inherited disorders affecting copper metabolism. Copper deficiency due to particularly high needs [prematurity (7,8) and recovery from severe PEM (9)(10)(11)(12)] or to very low intakes [non-copper-supplemented longterm total parenteral nutrition (13,14) and exclusive feeding with milk or milk-based formulas poor in copper (9,10,(14)(15)(16)(17)] has been documented. Finally, a few cases of hypocupremia have been reported in subjects with malabsorption due to long-lasting enteropathies (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral blood neutrophil count was the most sensitive parameter of copper depletion (15,(25)(26)(27). The initial absence of neutropenia in patient 1 could have been due to infection .…”
mentioning
confidence: 95%
“…The recommended daily dietary requirement of copper for a healthy adult is 0.9 mg. Copper is absorbed mainly through the small intestine, enters the liver through the portal vein and is partially excreted through the bile and mostly transported to different tissues and organs by binding to albumin and ceruloplasmin in the blood ( 3 ). In the 1950s, researchers found that copper deficiency causes hypocopperemia, hypoceruloplasminemia and neutropenia in infants ( 4 , 6 , 46 – 48 ) ( Figure 1 ). Following this, it was found that copper deficiency leads to impaired superoxide anion production by neutrophils, which kills bacteria ( 5 ).…”
Section: Relationship Between Copper and Immunitymentioning
confidence: 99%